Report on the Livestock Dynamics and Economic Resilience: A Comprehensive Modelling Framework Symposium at the 32nd International Conference of Agricultural Economists (ICAE) - Bahta, Sirak T. (2024)
The International Association of Agricultural Economists (IAAE) 2024 Symposium hosted a dedicated session on "Livestock Dynamics and Economic Resilience: A Comprehensive Modelling Framework." This session focused on recent innovations in livestock sector modeling, highlighting their role in evaluating threats to livestock populations, market access, livelihoods, and economic growth. The session presented findings from seven studies across different countries, employing diverse modeling approaches to improve livestock sector policies and investments. The session addressed some of the recent innovations made in livestock sector modeling. It highlighted how they can better evaluate the threats confronting livestock populations, market access, livelihoods, and economic growth. The session drew from and synthesized research from seven studies conducted across various countries using a range of complementary modeling approaches. The studies highlighted obstacles in livestock production, ranging from vulnerabilities to animal diseases to climate-induced shocks such as droughts and fluctuations in feed availability. These models aimed to improve the policy planning process, helping policymakers identify relevant investment options, animal health interventions (vaccination, quarantine, surveillance), and enabling policies and giving guidance to stakeholders in the various livestock chains on appropriate management and marketing that raise resilience.